Neuroprotective effect of Fn14 deficiency is associated with induction of the granulocyte-colony stimulating factor (G-CSF) pathway in experimental stroke and enhanced by a pathogenic human antiphospholipid antibody - Frauenknecht, Katrin Barbara Magda; Bargiotas, Panagiotis; Bauer, Henrike; Landenberg, Philipp von; Schwaninger, Markus; Sommer, Clemens (Journal of neuroimmunology, 2010)
Using a transgenic mouse model of ischemic stroke we checked for a possible interaction of antiphospholipid antibodies (aPL) which often cause thromboses as well as central nervous system (CNS) involvement under non-thrombotic conditions and the TWEAK/Fn14 pathway known to be adversely involved in inflammatory and ischemic brain disease. After 7days, infarct volumes were reduced in Fn14 deficient mice and were further decreased by aPL treatment. This was associated with strongest increase of the endogenous neuroprotective G-CSF/G-CSF receptor system. This unexpected beneficial action of aPL is an example for a non-thrombogenic action and the double-edged nature of aPL.
Gesehen am 19.06.2023